Formulation and Evaluation of Optimized Zaltoprofen Lyophilized Tablets by Zydis Technique - A. Hazzaa, Suray; N. Abd-Alhameed, Shaimaa (Iraqi Journal of Pharmaceutical Sciences, 2017)
â€œOrodispersible Tabletâ€ a tablet that is to be placed in oral cavity where it disperses rapidly by saliva with no need for water before swallowing. Zaltoprofen (ZLP) is one of NSAIDs which is used in the treatment of rheumatoid arthritis and osteoarthritis as well as to relieve inflammation and pain after surgery, injury and tooth extraction. The present study was aimed to prepare rapidly dissolved lyophilized Zaltoprofen tablet with different pharmaceutical excipients and studying the factors affecting pharmaceutical properties like (solubility, disintegration time DT, dissolution, etc.) of tablets. The lyophilized disintegrating tablets (LDTs) were prepared using Zydis technique by lyophilization an aqueous dispersion of Zaltoprofen with a matrix forming agent, gelatin, and a collapse protectant, glycine. In addition to many excipients like PVPK30 was used to improve the in vitro, in vivo disintegration time and dissolution rate, mannitol as bulk forming agent. Fourteen formulations were prepared to inspect the variables that affect the disintegration time and dissolution rate. All the formulations were evaluated for their physical appearance, mechanical strength, X-ray diffraction, FTIR, DT, and in vitro drug release. The prepared tablets were optimized and formula was subjected to different measured parameters such as disintegration time, Drug content, and in-vitro drug release. Results obtained from dissolution studies and DT showed that lyophilized disintegrating tablets (LDTs) (F8,F10,F12,F13 was 45,37,21 and 17 Sec.) respectively ,while(F14) displayed considerably faster in vitro dissolution rate of (Zaltoprofen) 3 min. and DT 9 sec. The (lyophilized disintegrating tablets) were also evaluated showing the transformation into amorphous state and absence of interaction of Zaltoprofen with the components of the tablets. From visual inspection ,physical strength ,DT and release behavior obtained ,one can conclude that the formulas(F14) which contains Zaltoprofen 3.2% ,gelatin3%, mannitol 3%, glycine 1.5%, PVP K30 1.5% was the most suitable one. Keywords : Zaltoprofen, lyophilization, PVPK30 .